In vitro antioxidant, antityrosinase, antibacterial and cytotoxicity activities of the leaf and stem essential oil from piper magnibaccum C. DC. - Hashim, Nur Athirah; Ahmad, Farediah; Jani, Nor Akmalazura; Darnis, Deny Susanti (Taylor and Francis, 2017)
The chemical composition of essential oils obtained from two parts of Piper magnibaccum C.DC. were analyzed by gas chromatography with a flame ionization detector (GC- FID) and gas chromatography- mass spectrometry (GC- MS). 25 components representing 93.5 % of the essential oil were characterized from the leaf of P. magnibaccum. The essential oil was dominated by germacrene D (40.8 %), β-caryophyllene (8.5 %) and α-cadinol (6.1 %). A total of 33 components, representing 87.6 % of the total oil were identified from the stem of P. magnibaccum. The major constituents were β-caryophyllene (19.7 %), germacrene D (10.7 %), and α- cadinol (8.2 %). The antioxidant potential of the leaf and stem essential oils of P. magnibaccum were determined on the basis of phenolic content and scavenging activity of the stable 1,1-diphenyl-2-picrylhydrazyl (DPPH) (IC50 20.5, 17.5 μg/mL) and 2,2’-azino-bis-3-ethylbenzothiazoline-6-sulphonic acid (ABTS) (IC50 11.7, 12.9 μg/ mL) free radicals. Antityrosinase activity of the leaf and stem were also screened using mushroom tyrosinase assay (I %= 49.50±0.6, 57.01±0.8). The essential oil of P. magnibaccum leaf showed a moderate antibacterial activity with MIC value of 250 μg/mL against P. aeruginosa. None of the essential oils exhibited acute cytotoxicity against MCF-7 and A-549 cells proliferation.